2016
DOI: 10.1002/brb3.587
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vector‐encoded microRNA‐based shRNA‐mediated gene knockdown of N‐methyl‐D‐aspartate receptors in skin reduces pain

Abstract: Background and Purpose RNA polymerase II promoters that drive the expression of rationally designed primary microRNA‐based shRNA, for example, shRNAmir, can produce more potent gene knockdown than RNA polymerase III promoters. Antagonists of peripheral N methyl‐D‐aspartate (NMDA) receptors that do not interfere with central glutamate processing would prevent the development of adverse central nervous system effects. Thus, in this study, we examined the effects of gene silencing and antinociception on formalin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that intrathecal delivery of an NMDA subtype 2B (NR2B)-mimetic peptide attenuates both neuronal hyperexcitability and abnormal pain-related behaviors by perturbing PSD-95-NR2B interactions 11 , 12 , suggesting that both proteins play an essential role in the generation of central sensitization. On the other hand, central sensitization is considered to contribute to the formation and development of chronic pain states 13 15 . However, the role and the underlying mechanism of the relationship between PSD-95 and NR2B in the development or maintenance of neuropathic pain are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that intrathecal delivery of an NMDA subtype 2B (NR2B)-mimetic peptide attenuates both neuronal hyperexcitability and abnormal pain-related behaviors by perturbing PSD-95-NR2B interactions 11 , 12 , suggesting that both proteins play an essential role in the generation of central sensitization. On the other hand, central sensitization is considered to contribute to the formation and development of chronic pain states 13 15 . However, the role and the underlying mechanism of the relationship between PSD-95 and NR2B in the development or maintenance of neuropathic pain are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of fluorescence sensors enabling the study of neuropeptides (Wang et al, 2023) in live behaving mice can allow us to determine how and when neuropeptides Substance P (product of tac1 gene) and Grp are released where the Tacr1 and Grpr are expressed in PBN and RVM. AAV-mediated delivery of silencing shRNAs (Liu et al, 2017; Rohn et al, 2024) targeting Tacr1 and Grpr can reveal the potential roles of these GPCRs in pain and itch. Notably, based on the results, the Tacr1 receptor and Tacr1-expressing neurons in the PBN and RVM can be targeted to modulate pain and itch.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies suggested that interfering with the miRNA expression in the skin affects the prognosis of diseases. For example, interfering NR1 subunit of the NMDA receptor by intradermally injecting lentiviral vector-encoded miRNA-based shRNA reduced inflammatory pain in rats 38. Intradermally injecting miR-129 and/or miR-335 agomirs into the wound edges accelerated wound healing in rats with diabetes 39.…”
Section: Discussionmentioning
confidence: 99%